Katakteristik pengembangan beras analog berbasis pati talas beneng (Xhantosoma undipes) dan jagung (Zea mays) dengan penambahan alginat (Sargassum sp): Characteristics of analog rice development based on taro starch (Xhantosoma undipes) andcCorn (Zea mays) with the addition of alginate (Sargassum sp) - Lubis, Nur Ikhwani; Haryati, Sakinah; Aditia, Rifki Prayoga (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Most Indonesian people are highly dependent on rice consumption to meet their daily carbohydrate needs. This results in a high level of rice consumption that exceeds its production level. This can have an impact on food security in Indonesia. Making analog rice from beneng taro starch, corn starch and the addition of alginate is possible as an alternative to rice, in addition analog rice can also be used as a high-fiber functional food. The purpose of this study was to determine the best alginate addition formulation for the characteristics of analog rice made from beneng taro starch and corn starch. This study used a Completely Randomized Design (CRD) with 1 alginate concentration factor consisting of four levels, namely 0%, 1%, 2%, and 3%. Each treatment was repeated three times so that a total of 12 experimental units were obtained. The results showed that the addition of 3% alginate gave the best results. Physical analysis showed that the best formulation had a rehydration power of 197% and a swelling power of 111%. Chemical analysis showed that the best formulation contained 0.86% fat, 2.14% protein, 13% water, 0.55% ash, 71.66% carbohydrate, and 6.25% dietary fiber. This fiber content contributed about 62.7% of the recommended daily fiber intake for the general population. In terms of sensory, the 3% alginate formulation was also the most preferred by the panelists, especially in terms of appearance, odor, taste, and texture.